Ethnobotanical applications of Aloe vera (L.) Burm. f. (Asphodelaceae) in Piauí, Northeastern Brazil: a review - Silva, Polyana Cristina Araújo da; Oliveira, Ykaro Richard; Pacheco, Ana Carolina Landim; Marques, Márcia Maria Mendes; Abreu, Maria Carolina de (Ethnobotany Research and Applications, 2020)
Background: Ethnobotanical studies are an important tool for traditional knowledge rescue and valorization, indicating how community members use the plants for food, construction, rituals, and medicine. Aloe vera is widely used as medicinal herb throughout Brazil, besides that, the investigation of how local communities are related to available plant resources is relevant for the construction of new knowledge and also for the improvement of these uses. Thus, the aim of this work was to point out the applications of Aloe vera in the state of Piauí, northeastern Brazil. Methods: For this review, the databases SciELO, Science Direct, Pubmed and Web CAPES were used. Books and articles were selected, comprising aspects directly or indirectly involved in ethnobotanical and ethnobiological research at Piauí, following the time frame from 2010 to 2019. Information related to the research location, data collection and the main results obtained about the uses of the plant were listed in the selected manuscripts. The main descriptors used were: Aloe vera, medicinal plants, pharmacological properties and traditional medicine. Results: Were recorded 35 ethnobotanical studies carried out in Piauí, which 23 cited the use of Aloe vera in the communities studied. The application of the referred species being mentioned in 24 cities. In Piauí, this species has been reported as a medicinal herb, cosmetic product, in veterinary medicine and also for magical-religious purposes. Aloe vera had its application registered in the treatment of gastrointestinal disorders; respiratory disorders; as a healing agent, against skin injuries; in the treatment of hemorrhoids and also as an anthelmintic, anti-inflammatory, antitumor and antifungal. Some studies indicate certain chemical compounds contained in Aloe vera as efficient in the treatment of several diseases for which this species is used as medicinal herb in Piauí. Conclusions: Aloe vera species is frequently cited in ethnobotanical studies carried out in Piauí, evidencing the considerable cultivation of this plant in several communities throughout the state. Keywords: South America, biological activities, medicinal plants, pharmacological properties.